The impact of Covid-19 on the Mental Health of the Portuguese Population - I. Dos Santos; J. Saraiva; E. Mesquita; M. Coelho (European Psychiatry, 2022)
Introduction Covid-19 does not only have repercussions on the physical level, representing a new way of life, both individually and in society. The pandemic results in invisible consequences for the population’s mental health.